Development and evaluation of a new bicycle instrument for measurements of pedal forces and power output in cycling - Stapelfeldt, B.; Mornieux, G.; Oberheim, R.; Belli, A.; Gollhofer, A. (International Journal of Sports Medicine, 2007)
Determination of pedal forces is a prerequisite to analyse cycling performance capability from a biomechanical point of view. Comparing existing pedal force measurement systems, there are methodological or practical limitations regarding the requirements of scientific sports performance research and enhancement. Therefore, the aim of this study was to develop and to validate a new bicycle instrument that enables pedal forces as well as power output measurements with a free choice of pedal system. The instrument (Powertec®-System) is based on force transducer devices, using the Hall-Effect and being mounted between the crank and the pedal. Validation of the method was evaluated by determining the accuracy, the cross talk effect, the influence of lateral forces, the reproducibility and, finally, a possible drift under static conditions. Dynamic tests were conducted to validate the power output measurement in reference to the SRM-System. The mean error of the present system was - 0.87 ± 4.09 % and - 1.86 ± 6.61 % for, respectively, the tangential and radial direction. Cross talk, lateral force influence, reproducibility and drift mean values were < ± 7 %, = 2.4 %, < 0.8 % and 0.02 N · min-1, respectively. In dynamic conditions, the power output measurement error could be kept below 2.35 %. In conclusion, this method offers the possibility for both valid pedal forces and power output measurements. Moreover, the instrument allows measurements with every pedal system. This method has an interesting potential for biomechanical analyses in cycling research and performance enhancement.